2016
DOI: 10.1038/mp.2016.193
|View full text |Cite
|
Sign up to set email alerts
|

Hypervulnerability of the adolescent prefrontal cortex to nutritional stress via reelin deficiency

Abstract: Overconsumption of high-fat diets (HFDs) can critically affect synaptic and cognitive functions within telencephalic structures such as the medial prefrontal cortex (mPFC). The underlying mechanisms, however, remain largely unknown. Here we show that adolescence is a sensitive period for the emergence of prefrontal cognitive deficits in response to HFD. We establish that the synaptic modulator reelin (RELN) is a critical mediator of this vulnerability because (1) periadolescent HFD (pHFD) selectively downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 76 publications
7
56
1
1
Order By: Relevance
“…Both antibodies showed cellular and structural stain patterns consistent with previews observations of their intended targets (Brederode, Helliesen, & Hendrickson, ; Carceller, Rovira‐Esteban, Nacher, Castrén, & Guirado, ; Carlos et al, ; Labouesse et al, ). Secondary antibodies did not show any obvious stain when tested without primary antibodies.…”
Section: Methodssupporting
confidence: 77%
“…Both antibodies showed cellular and structural stain patterns consistent with previews observations of their intended targets (Brederode, Helliesen, & Hendrickson, ; Carceller, Rovira‐Esteban, Nacher, Castrén, & Guirado, ; Carlos et al, ; Labouesse et al, ). Secondary antibodies did not show any obvious stain when tested without primary antibodies.…”
Section: Methodssupporting
confidence: 77%
“…A growing body of literature has shown adolescence to be a critical period where exposure to alcohol (Gass et al, ; Nasrallah, Yang, & Bernstein, ; Schindler, Tsutsui, & Clark, ), psychostimulants (Hammerslag, Waldman, & Gulley, ; Sherrill, Stanis, & Gulley, ), cannabinoids (Schneider, Schomig, & Leweke, ), and high fat or high sugar diet (Boitard et al, ; Labouesse et al, ) has pronounced and enduring detrimental effects on cognition, behavior, and learning. In particular, memory tasks reliant on the hippocampus are rapidly disrupted by high fat and high‐sugar diets (Abbott, Morris, Westbrook, & Reichelt, ; Kanoski & Davidson, ; Kanoski, Meisel, Mullins, & Davidson, ), and emerging data links consumption of high fat and high‐sugar diets to deficits in cognition facilitated by the PFC (Baker & Reichelt, ; Labouesse et al, ). The neural basis of these diet induced cognitive deficits has been largely reviewed (Kanoski & Davidson, ; Morris, Beilharz, Maniam, Reichelt, & Westbrook, ).…”
Section: Diet‐induced Alterations In Reward Neurocircuitrymentioning
confidence: 99%
“…Studies with obese adolescents have reported deficits in several aspects of executive functioning, which in turn have been further linked to a reduction in the volumes of frontal cortical regions, including the PFC (Lokken, Boeka, Austin, Gunstad, & Harmon, ; Maayan, Hoogendoorn, Sweat, & Convit, ). In a highly controlled study that examined the cognitive effects of consumption of a high fat diet during adolescence and during adulthood in mice, adolescent mice were more impaired at PFC‐mediated cognitive tasks than adult mice (Labouesse et al, ). This included working memory processes, in particular the ability to maintain the performance of behavioral tasks over a delay, and inhibition of a response to an aversive stimulus (Labouesse et al, ).…”
Section: Diet‐induced Alterations In Reward Neurocircuitrymentioning
confidence: 99%
“…Of note, some deep cortical Martinotti cells express reelin (Pesold et al, 1999) and constitute one of the main sources of secreted reelin in neocortical superficial layers (Ramos-Moreno and Clasca, 2014). Thus, GABAergic impairment and disruption of the E/I balance observed in HRM could have deleterious effects on the function of cortical circuits such as the dendritic filtering of inputs and encoding of stimuli and ultimately in the processing of information and behavioral adaptation (Barr et al, 2008; Teixeira et al, 2011; Labouesse et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…One distinctive feature of the PFC is its protracted maturation through early adulthood (Gogtay et al, 2004) characterized by connectivity refinement in parallel to maturation of cognitive abilities (van Eden et al, 1990; Luna et al, 2001). This extended period of maturation constitutes a sensitive period of increased vulnerability to injuries leading to development of neurophychiatric disorders (Lewis, 1997; McEwen and Morrison, 2013; Iafrati et al, 2016; Labouesse et al, 2016). Several studies suggest that alterations of postnatal PFC maturation may contribute to the development of psychiatric diseases including depression, addiction, ASD and schizophrenia (Lewis, 1997; Raedler et al, 1998; Iafrati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%